Fabrication of polyaniline nanorods on electro-etched carbon cloth and its electrochemical activities as electrode materials - Razali, Shaifulazuar; Rusi, -; Majid, Siti Rohana (Springer Verlag (Germany), 2019)
In this work, polyaniline (PANI) nanorods were deposited on electro-etched carbon cloth (EC) by facile electrodeposition method with the existence of purified aniline and sulfuric acid. Various deposition potentials were applied to achieve a good electrochemical performance of EC-PANI electrode. Different applied potentials resulted in different morphologies of PANI deposits and studied by field emission scanning electron microscope (FESEM) and transmission electron microscope (TEM). X-ray diffraction (XRD) and Fourier transform infrared (FTIR) characterizations were used to confirm the deposition of PANI on the EC substrate. The optimized PANI nanorods electrode exhibited an excellent specific capacitance of 357.14 Fg−1 with an energy density of 40.18 Wh kg−1 and a power density of 1.28 Wkg−1 at a current density of 0.5 Ag−1 in 0.5 M H2SO4 electrolyte. A symmetrical cell of P1.4//PVA + 0.5 M H2SO4//P1.4 has recorded a good cycling stability with 95 and 88% capacitance retention at current densities of 200 and 300 mAg−1. EC-PANI electrode can be used as a scalable solution for high-performance energy storage devices. © 2018, Springer-Verlag GmbH Germany, part of Springer Nature.